Comparison of Postoperative Loss of Reduction after Percutaneous Kirschner Wire Fixation and Conservative Approach in Displaced Distal Radius Fracture in Children - Muhammad Nabeel Sabir, Rana Muhammad Adnan, Muhammad Sharjeel Sabir, Muhammad Omer Kaleem (Journal of Rawalpindi Medical College, 2018)
Background: To compare frequency of post-operative loss of reduction in percutaneous Kirschner wire fixation and conservative approach in displaced extra-articular non-physeal distal radius fractures in children. Methods: In this comparative study children of age 5-15 years, with displaced extra-articular non-physeal distal radius fractures, were included. Patients were divided in two groups randomly on basis of lottery method. In group A, patient were operated with closed reduction and percutaneous Kirschner wire fixation using fluroscope. In group B, patients were conservatively managed in cast after closed reduction under flouroscope by the senior orthopedic surgeon. Postoperative loss of reduction in both groups was recorded. Follow-up conducted at 2nd and 4th week and loss of reduction was observed radiologically . The loss of reduction was recorded on study performa by the researcher trainee. Chi square test was applied to compare the difference between the loss of reduction in two groups. Effect modifiers like age, gender, unilateral or bilateral was controlled by stratification. Post stratification Chi square test was applied. P-value < 0.05 was considered statistically significant. Results: Out of 60 patients, 28 (46.7%) were male children.The mean age of the patients in our study was 10.18±3.372 years. Loss of reduction of reduction was observed 50 times more in conservative approach as compared to operative patients. Conclusion: The postoperative loss of reduction is less common in displaced extra-articular non-physeal distal radius fracture in children after percutaneous kirschner wire fixation as compared to fractures treated by conservative approach.